Batch and Flow-Injection Spectrophotometric Determination of Procaine HCl in Pharmaceutical Preparations Via Using Diazotization and Coupling Reaction - Baghdad Science Journal (مجلة بغداد للعلوم)
Simple and sensitive batch and Flow-injection spectrophotometric methods for the determination of Procaine HCl in pure form and in injections were proposed. These methods were based on a diazotization reaction of procaine HCl with sodium nitrite and hydrochloric acid to form diazonium salt, which is coupled with chromatropic acid in alkaline medium to form an intense pink water-soluble dye that is stable and has a maximum absorption at 508 nm. A graphs of absorbance versus concentration show that Beer’s law is obeyed over the concentration range of 1-40 and 5-400 µg.ml-1 of Procaine HCl, with detection limits of 0.874 and 3.75 µg.ml-1 of Procaine HCl for batch and FIA methods respectively. The FIA average sample throughput was 70 h-1. All different chemical and physical experimental parameters that affecting on the development and stability of the colored product were carefully studied and the proposed methods were applied satisfactorily for the determination of Procaine HCl in an injections samples using the standard addition method.